Necrotizing Enterocolitis, Sepsis, dan Diare Akibat Alergi Susu Sapi pada Bayi Cukup Bulan dengan Hipotiroidisme - Runi Arumndari; Asterisa Retno Putri; Claudia Natasha Liman; Putu Siska Suryaningsih (Cermin Dunia Kedokteran, 2024)
Necrotizing enterocolitis (NEC) remains one of the most common gastrointestinal diseases in neonates, with high morbidity and mortality. An 8-day-old full-term baby girl was admitted with an initial diagnosis of sepsis and acute diarrhea due to a cow’s milk allergy. Her condition worsened on the 4th day of hospitalization with abdominal distention, bradypnea, and vomiting. An abdominal x-ray showed increased bowel gas. She had a slightly lowered FT4. The findings met Bell’s criteria for the diagnosis of NEC. After being given meropenem and levothyroxine for 7 days, she was discharged on the 12th day of hospitalization in good condition. NEC is allegedly to be a multifactorial disease, with predisposing factors of cow’s milk formula (CMF) feeding or not breast-fed since birth, sepsis, and hypothyroidism. The combination of clinical symptoms, radiologic findings, and risk factor tracing is important in the diagnosis and management of NEC.